Application of "Automotive Painting" Job Sheet Based on Direct Instruction in the "Painting Technology" Course on Sheet Metal Media - Muh. Bhilal Halim (Journal of Electrical Engineering and Informatics, 2026)
The Painting Technology course in the Automotive Engineering Education Study Program, Faculty of Engineering, Universitas Negeri Makassar (UNM) requires students to master practical painting skills. However, a gap between theory and practice still exists. This study applies an "Automotive Painting" job sheet based on the direct instruction (DI) model to improve practical learning outcomes on sheet metal media. A quantitative descriptive approach with a one-shot case study design was employed. The subjects were 20 students in the even semester of 2025/2026 enrolled in the Painting Technology course. The course was conducted over 16 meetings (5 theory+demonstration, 2 midterm/final exams, 8 practicum sessions using DI-based job sheets). Instruments included observation sheets, product assessment rubrics (30×40 cm sheet steel panels), student response questionnaires, and quality measurements (gloss meter, coating thickness gauge, cross-cut adhesion test). Data were analyzed descriptively. Results: The average student practicum score reached 84.6 (scale 100) with a mastery rate of 95%. The most common defects were dust nibs (40% of panels) and mild orange peel (25%), which could be corrected during the finishing stage. Final product quality showed an average gloss value of 86 GU (60°), coating thickness of 122 µm, and adhesion category 4B (ASTM D3359). Student responses to the DI-based job sheet were very positive (91% agreed that the job sheet was easy to follow). This study provides the first empirical evidence of the application of an "Automotive Painting" job sheet based on direct instruction in a painting technology course at a university with a large class size in Eastern Indonesia.